The Quality of Life of Type 2 Diabetes Mellitus Patients in Timor Ethnicity at Pasir Panjang Health Center, Kupang City - Fransiskus Salesius Onggang (Aloha International Journal of Health Advancement (AIJHA), 2018)
Diabetes mellitus (DM) is one of the most common chronic diseases found in the 21st century. Data of the Pasir Panjang Public Health Center in 2017 showed that the incidence of Diabetes Mellitus that did not depend on insulin in the inpatient room was 91 people, with 10 dead patients. The amount is based on age, from 25 to 44 years, 1 man and 8 women; age 45-64 years, 22 men and 40 women; age over 65 years, 8 male and 11 female. The prevalence of DM-dependent non-insulin events with gangrene in Pasir Panjang Health Center in 2013 was 1 woman with age 54 years. In 2015 there were an increase of 8 people with the age of 45 - 64 years, with the number of men as many as 3 people. The purpose of this study was to determine the relationship between family support and the quality of life of people with Type 2 diabetes mellitus in ethnic Timor, at the Pasir Panjang Public Health Center, Kupang City. This research utilized cross sectional approach. The sample was Type 2 DM sufferers and their families, with a sample size of 52, which was selected by accidental sampling technique. Categorical data that have been collected are analyzed descriptively in the form of frequencies and percentages and are presented in tabular form. Then the hypothesis test was performed using the Chi-Square test. Chi-square test results showed a p-value of 0.045 so it was concluded that there was a relationship between family support and the quality of life of people with Type 2 DM in Pasir Panjang Public Health Center, Kupang City. Keywords: type 2 diabetes mellitus, family support, quality of life